Impact of the Camp David accords on the Saudi-Egyptian relations (International relations and international law Journal, 2016)
The paper offers an analysis of the main aspects of Saudi-Egyptian relations during the time of the Camp David Accords. Problems, which complicated relations between Saudi Arabia and Egypt at the turn of the 1980ies are identified. Describes results of Camp David Accords and peace treaty which signed in Washington on march 26 1979 between Egypt and Israel. As well as impact of agreement on international situation in the Middle East and including a description of Egypt’s relations with the Arab world.
Keywords: Middle-East conflict; Camp David Accords; Saudi-Egyptian relations; Arab-Israili war; political isolation; Egyptian-Israeli peace treaty